2023
DOI: 10.1021/acs.est.3c04690
|View full text |Cite
|
Sign up to set email alerts
|

Armoring of MgO by a Passivation Layer Impedes Direct Air Capture of CO2

Juliane Weber,
Vitalii Starchenko,
Ke Yuan
et al.

Abstract: It has been proposed to use magnesium oxide (MgO) to separate carbon dioxide directly from the atmosphere at the gigaton level. We show experimental results on MgO single crystals reacting with the atmosphere for longer (decades) and shorter (days to months) periods with the goal of gauging reaction rates. Here, we find a substantial slowdown of an initially fast reaction as a result of mineral armoring by reaction products (surface passivation). In short-term experiments, we observe fast hydroxylation, carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, there is also no evidence of crystallinity in the BF-TEM images. Further research is needed to conclusively determine if the reaction layer is a crystalline phase or not, but previous studies have observed precipitation of amorphous magnesium hydroxide during reactions between magnesium sulfate and calcium hydroxide, as well as precipitation of amorphous phases during the reaction of MgO in ambient conditions for time periods shorter than 2 months. ,, …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is also no evidence of crystallinity in the BF-TEM images. Further research is needed to conclusively determine if the reaction layer is a crystalline phase or not, but previous studies have observed precipitation of amorphous magnesium hydroxide during reactions between magnesium sulfate and calcium hydroxide, as well as precipitation of amorphous phases during the reaction of MgO in ambient conditions for time periods shorter than 2 months. ,, …”
Section: Resultsmentioning
confidence: 99%
“…This implies the changes in density arise from reactions driven by water and its dissociation products, which may be able to continue accessing the reaction layer interface due to the roughness, nonuniformity, and/or permeability of the reaction layer observed with XRR and AFM. Since the longer-term reactions of Weber et al show evidence for crystallinity, the changes in density may be due to the reaction layer restructuring toward a more crystalline phase, presumably through the release of structural water …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations